An Analysis of Word Formation in Ariana Grande Song Lyrics from The Album “Sweetener” - Yola Alghasani; Rusdi Noor Rosa (Universitas Negeri Padang, 2022)
This study aimed to analyze Ariana Grande‟s song lyrics in the album “Sweetener”. This study used a descriptive research method. The result of word formation used in song lyrics showed that there is one word formation process of the borrowing type. In the second aspect, the word formation of the coinage process appears two data. In the third aspect, the word formation of the compounding process appears five data. In the fourth aspect, the word formation of the mixing process appears seven data. In the fifth aspect, the word formation of the clipping process appears three data. In the eighth aspect, the word formation of the inflection process appears five as in compounding and the last, the word formation of derivation appears six data.